Editorial: 200 years after the revolution (1820-2020) - Subtil, J.; Atallah, C.; Mota, S.; Dominguez, R. da C. (Janus.net, 2021)
In 2020, we highlighted the 200 years of the Liberal Revolution, one of the essential historiographical landmarks in the History of Portugal and Brazil. We did this by organizing an inter-university webinar that was attended by researchers from both sides of the Atlantic. In the words of German historian Sebastian Conrad, the organizers strove to create a broad and universal approach to this historic event, bypassing the pitfalls of Eurocentrism and biased interpretations with a perspective linked to the development of the «nation-states» of the 19th century. In this sense, the participation of different specialists in the various panels was essential, allowing the participants and, consequently, the readers of this thematic issue of the janus.net journal, to have a comparative, balanced and multilateral view. This view encompasses both issues directly related to the Portuguese context, immediately before and after the revolution, and aspects regarding its developments and impacts in different contexts, in different chronologies and in different parts of the Atlantic.